Reconceptualizing Trust in Islamic Marketing: A Systematic Review of Attitudes and Purchase Intention - Sukoco, Hendro; Krisnaresanti, Aldila; Kayadibi, Sahnoza (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to provide a comprehensive overview of consumer behavior in the context of Islamic marketing by systematically reviewing existing literature on attitudes, trust, and purchase intention. As Islamic markets expand globally, understanding the psychological and behavioral drivers that shape Muslim consumer decision-making has become increasingly important. This review synthesizes articles published over the last decade (2015–2025) indexed in major scientific databases, focusing on empirical and conceptual studies related to halal products, services, and Islamic branding. The findings reveal that consumer attitudes are strongly influenced by religious commitment, halal awareness, and perceived product quality. Trust emerges as a central determinant, particularly shaped by halal certification, corporate credibility, and transparency of marketing practices. Moreover, purchase intention is found to be mediated by consumer trust and moderated by socio-cultural factors such as religiosity, lifestyle, and generational differences. The review highlights methodological trends, including the dominance of survey-based quantitative approaches and the growing application of structural equation modeling. Despite substantial progress, research gaps remain in exploring digital platforms, sustainability issues, and cross-cultural comparisons of Muslim and non-Muslim consumers. This paper contributes by mapping the intellectual landscape of Islamic consumer behavior and offering directions for future research in the era of global halal markets.